Efficacy and safety of fixed-combination bimatoprost/timolol ophthalmic solution - Moon SB; Han SB (Patient Preference and Adherence, 2017)
Suk Bae Moon,1 Sang Beom Han21Department of Surgery, Kangwon National University Hospital, Kangwon National University Graduate School of Medicine, Chuncheon, Korea, 2Department of Ophthalmology, Kangwon National University Hospital, Kangwon National University Graduate School of Medicine, Chuncheon, KoreaWe read, with interest, the article by Sun et al1 entitled “Patient satisfaction with fixed-combination bimatoprost/timolol ophthalmic solution: a survey study in patients with glaucoma in China”. This observational multicenter study with excellent design was undoubtedly well conducted, and the authors successfully demonstrated that fixed-combination bimatoprost/timolol ophthalmic solution can provide the glaucoma patients with improved satisfaction.1View the original paper by Sun and colleagues.